Autotoxins in continuous tobacco cropping soils and their management - Chen, Yudong; Yang, Long; Zhang, Lumin; Li, Jianrong; Zheng, Yalin; Yang, Wenwu; Deng, Lele; Gao, Qian; Mi, Qili; Li, Xuemei; Zeng, Wanli; Ding, Xinhua; et al. (Frontiers in Plant Science, 2023)
Tobacco belongs to the family Solanaceae, which easily forms continuous cropping obstacles. Continuous cropping exacerbates the accumulation of autotoxins in tobacco rhizospheric soil, affects the normal metabolism and growth of plants, changes soil microecology, and severely reduces the yield and quality of tobacco. In this study, the types and composition of tobacco autotoxins under continuous cropping systems are summarized, and a model is proposed, suggesting that autotoxins can cause toxicity to tobacco plants at the cell level, plant-growth level, and physiological process level, negatively affecting soil microbial life activities, population number, and community structure and disrupting soil microecology. A combined strategy for managing tobacco autotoxicity is proposed based on the breeding of superior varieties, and this approach can be combined with adjustments to cropping systems, the induction of plant immunity, and the optimization of cultivation and biological control measures. Additionally, future research directions are suggested and challenges associated with autotoxicity are provided. This study aims to serve as a reference and provide inspirations needed to develop green and sustainable strategies and alleviate the continuous cropping obstacles of tobacco. It also acts as a reference for resolving continuous cropping challenges in other crops.